ANALISIS PENDAPATAN USAHATANI DAN PEMASARAN GAMBIR - JT. Yuhono (Buletin Penelitian Tanaman Rempah dan Obat, 2004)
Benefit and marketing analysis of gambier were conducted at Manggilang village, district Pangkalan Kotobaru, 50 kota regency, West Sumatera province, from August to September 2003. The study was aiming at the performance, and marketing benefit of gambier farming system. The study was performed with survey method, where the sample of Manggilang village was selected purposely since it was the center of gambier production. Farmer respondent was determined by mean of simple random sampling, the performance of farming system with deskriptive analysis and the marketing system with margin analysis. The result showed that the farming system, cultivation and processing were conducted traditionally, which was one of the factors that cause the low quality, rendemen and benefit. The benefit from total cost was Rp. 4.840.625,- per hectare per year, while the benefit from cash cost was Rp. 6.238.125,- per hectare per year. The B/C ratio form total cost was 1,69 and cash cost was 2,11. The marketing system was efficient, showed by the high farmer price margin (67%). The marketing marjin between marketing institutions was balanced (12,49% - 20,88%) and the profit of marketing institutions was in the range of 10 – 20%.